Peran Digitaliasi dalam Membangun Literasi Inklusi Pasar Modal - Novita Hajar; Alfathisya Regina Putri Bahri; Rudi Sanjaya (International Forum of Researchers and Lecturers, 2024)
Digitalization has played a significant role in improving capital market inclusion literacy in Indonesia. In the era of digital transformation, financial literacy is an important element for people to manage their finances wisely and maximize the use of investment products. This study aims to examine how digitalization affects people's investment behavior through increasing financial literacy and accessibility of financial services. Using a literature study method, this article collects information and data from various sources to explore the impact of digitalization on investment behavior. The results show that financial literacy allows people to understand the risks and opportunities in the capital market, while financial inclusion ensures easier access to financial services. Digitalization accelerates investment adoption, especially among people who were previously less educated about the capital market.